The first Christian hymnal: the songs of the ancient Jerusalem church ; parallel Georgian-English texts - Shoemaker, Stephen J. (Eastern Christian texts, 2018)
"This book offers the first English translation of the earliest Christian hymnal, a little-known and overlooked text that preserves the sacred songs of Jerusalem’s Christian communities during the late fourth or early fifth century. This hymnal, known as the Jerusalem Georgian Chantbook, preserves the hymnography of the Jerusalem churches from a crucial moment in early Christian history, when Christianity was transitioning from a small minority faith into the faith of an empire. This book presents the hymns that were used for regular Sunday worship. These hymns not only are the oldest part of the collection, but they also would have had the most influence in forming the faith of Jerusalem’s congregations. " --